Changing the conventional university classroom - Sengupta, Enakshi; Blessinger, Patrick 1964- (Innovations in higher education teaching and learning, 2022)
Changing the Conventional University Classroomhighlights the interventions practiced around the world by higher education instructors forced to make necessary changes in the conversion from face-to-face educational instruction to the use of online and virtual platforms during the COVID pandemic